MEETING PARENTS’ ASPIRATIONS: ENHANCING TEACHING AND LEARNING FOR INFANTS AND TODDLERS IN TASKA - DAYANG INTAN FARAHIAH ALMURID; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study explores parents’ aspirations and expectations for teaching and learning approaches in TASKA (childcare centres) for children aged 12 to 36 months. The research aims to identify how parents perceive the effectiveness of play-based learning and the overall quality of early childhood education provided. A survey using Google Forms was conducted with 20 parents as respondents. Data were collected using a Likert scale and analyzed to determine trends in parental expectations. Findings reveal that parents prioritize holistic development, emphasizing independence, communication, social skills, and emotional growth. They also value a safe and caring environment with well-trained teachers who use interactive and age-appropriate learning activities. The study recommends that TASKA strengthen communication with parents, enhance teacher training in early childhood development, and provide a balance between play-based, outdoor, and academic learning. These efforts will ensure that early education aligns with parental aspirations and supports children’s overall well-being.